Genetic control of qualitative and quantitative traits in bell pepper crosses involving varied fruit colors and shapes. Issue 5 (3rd September 2022) - Banerjee, Swadesh; Bhattacharjee, Tridip; Maurya, Praveen Kumar; Mukherjee, Debmala; Islam, Sk Masudul; Chattopadhyay, Arup; Ghosh, Dipak Kumar; Hazra, Pranab
ABSTRACT: Genetic improvement of fruit color and shape of bell pepper ( Capsicum annuum var. grossum Sendt.) have been constrained by lack of adequate information on genetic control of fruit physical-chemical characteristics at the physiologically mature stage. Inheritance pattern of fruit color and shape and the nature of gene action for quantitative traits at physiological maturity were studied in six genetic populations (P1, P2, F1, F2, BC1 P1, BC2 P2 ) generated from four crosses involving parents bearing different fruit color and shape. Duplicate recessive epistasis gene action was involved in the expression of fruit color in Red × Yellow cross. The segregation pattern of the crosses Red × Purple and Red × White indicated involvement of dominant and recessive epistasis, respectively. Fruit shape segregation of the cross Blocky × Elongate indicated recessive epistasis gene interaction. The inheritance pattern indicated that fruit color and shape in bell pepper were conditioned by two genes with either dominant or recessive epistatic action. The segregation pattern of test crosses revealed involvement of two loci; there is no linkage between the genes and their two alternative alleles on both the loci. Gene action of most of the quantitative characters in the crosses 'C/4 × 8/4ʹ and 'C/4 × BC CAP Yellow' indicated predominance of non-additive gene action showing duplicate epistasis. Fruit color and shape were conditioned by two genes showing either dominant or recessive epistatic action, however, these two characters were not linked. Fruit physical and chemical traits could be improved following deferred selection through advancement of promising cross-combination.